The Effect of Brainstorming Learning Model to Increase Economic Learning Outcomes of Students of Class XI IPS MA Al-Jam'iyatul Washliyah Tembung - Ihsan Nurfaizi B. Manalu; Dalmi Iskandar Sultani (Budapest International Research and Critics University, 2022)
Research Title: The Effect of Brainstorming Learning Model to Improve Economics Learning Outcomes of Class XI Social Sciences MA AL-Jam'Yatul Washliyah Tembung FY 2021/2022. This study aims to see the effect of the BrainStorming learning model on student learning outcomes.This type of research is pre-experimental using One Group Posttest Pesearch Design. The population and sample in this study were the entire class of XI IPS students of Al-Jam'Yatul Washliyah Tembung. The sample of this study was 1 class. The results of the study showThe calculated t value obtained is 5.26 and we compare the t table value of 0.91, 5.26> 0.91. So it can be interpreted that the brainstorming learning model has a positive and significant impact on improving economic learning outcomes for class XI IPS2 Al-Jam'Yatul Washliyah Tembung.